If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -6(2a + 3) = 42 Reorder the terms: 7 + -6(3 + 2a) = 42 7 + (3 * -6 + 2a * -6) = 42 7 + (-18 + -12a) = 42 Combine like terms: 7 + -18 = -11 -11 + -12a = 42 Solving -11 + -12a = 42 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -12a = 42 + 11 Combine like terms: -11 + 11 = 0 0 + -12a = 42 + 11 -12a = 42 + 11 Combine like terms: 42 + 11 = 53 -12a = 53 Divide each side by '-12'. a = -4.416666667 Simplifying a = -4.416666667
| -33(12x)+29(21x)=(73-73)+(-737+98) | | -4j+10=-5j | | -15+m=4 | | -3f=8+f | | 2(6b-3)=-78 | | 3(x+7)=-6x-33 | | -19j-20=-6j-15j+18 | | 18=-2x-7x | | -20=31+3x | | 6b-12b+4c+6d= | | 2(x-5)3x=20 | | x+5x-7x+3-x=48 | | 1-(3y+3)=-8 | | -5q-10=-6q | | 4q-3y=27 | | 19-16-17h=-7-18h | | 1-3y+3=-8 | | -38(15x)+28(24x)=(75-75)+(-608+98) | | 5(3x-4)-3=5(x-2)+37 | | 8k=9+7k | | 10m+4=74mis | | -7-2x=2 | | -8d+6=20-10d+18 | | -9m=9-10m | | 24=8(x+2) | | -x+4+4=13 | | 2x(x-3)=18x^2-7x | | -608+98= | | -3(s+17)=-15 | | 9x-126=2x+49 | | -5(1+3x)=70 | | 19.9u+19.89=17.46-4.42+19.4u |